Challenges and opportunities of decarbonization for the economic recovery post-pandemic: The question of directionality in innovation policies - Bento, N.; Fontes, M.; Barbosa, J.; Mamede, R.P. (Entre transições: retrospetivas – transversalidades – perspetivas, 2022)
Countries face a double challenge of unprecedented scale consisting on drastically reducing carbon emissions in the time of a generation, while recovering the economy from the worst pandemic crisis in a century. Innovation is key in the response to this double challenge. Innovation policies are increasingly directed at achieving both goals, as governments seek opportunities for transforming the economic structure along with decarbonization. We raise the question of the effect of the direction in the success of the policies for the sustainability transition to achieve the economic transformation. We start by analyzing the processes of change in the economic structure. We identify three possible strategies of transformation: decarbonization, dematerialization and digitalization. Then we compare the evolution of the economic complexity of Portugal, which aspires to transform its economy, with that of three countries that are respectively reference in each one of the three strategies: Denmark, The Netherlands, and Ireland. Successful strategies evidence specialization in products that involve extensive and sophisticated knowledge, produced with high connectivity to other activities and with low carbon footprint. Based on these results and informed by the theory, we propose a set of conditions—related to the promotion of connectivity to growing sectors, high social return technologies and variety—that need to be aligned in the direction of the policies in order to increase their potential for transformative change.